CUSTOMER SATISFACTION ANALYSIS: Image and Service Perspectives at Indonesian Insurance - Maria Ulfah (Universitas Pamulang, 2022)
In the insurance business the most important thing is consumer trust, and to build it is to provide satisfaction. Thus, various efforts have been made to satisfy consumers, including by providing excellent service and maintaining the credibility of the company. This study attempts to analyze consumer satisfaction in the insurance sector, with company image and service as influencing variables. In studying scientifically, a quantitative method with a probability analysis technique is determined, namely multiple linear regression. The object of this research is PT Airline Reasuransi Indonesia, and the respondents are customers, as many as 118 people. Data were obtained through the distribution of questionnaires which were conducted randomly. The results of the study explain that the principle of choosing insurance is the credibility of the company or image, then service, especially with regard to the breadth of the network of cooperation with the hospital and the ease of claims.Keywords: Insurance, Image, Excellent Service, Satisfaction